WORD FORMATION PROCESSES IN ENGLISH NEW WORDS OF OXFORD ENGLISH DICTIONARY (OED) ONLINE - Ratih, Elisa; Gusdian, Rosalin Ismayoeng (University of Muhammadiyah Malang, 2018)
The aims of this study were to identify the processes of word formation in English new words and to know which word formation processes were the most productive one(s). The researcher used qualitative research design in order to obtain the data from the document of OED online. OED online is the online dictionary which consists of list of English new words. Therefore, the research object was the lists of English new words from year 2012-2016. Document analysis was used as the instrument to collect the data. The data were presented in the form of table. The findings of this study showed that there are some processes in creating English new words, such as a) affixation, b) folk etymology, c) compounding, d) abbreviation, e) acronyms, f) borrowing, g) blending, h) clipping, i) back-formation. Besides, there are also found the double word formation processes, such as j) folk etymology + compounding, k) compounding + affixation, m) blending + affixation, n) clipping + blending. The result showed that the most productive process of creating English new words was affixation.